Improved clinical outcome following liver transplant in patients with ethylmalonic encephalopathy. Issue 6 (12th March 2019) - Tam, Allison; AlDhaheri, Noura Salem; Mysore, Krupa; Tessier, Mary Elizabeth; Goss, John; Fernandez, Luis A.; D'Alessandro, Anthony M.; Schwoerer, Jessica Scott; Rice, Gregory M.; Elsea, Sarah H.; Scaglia, Fernando
Abstract : Ethylmalonic encephalopathy (EE) is a rapidly progressive autosomal recessive mitochondrial disease caused by biallelic pathogenic variants in the ETHE1 gene that encodes the mitochondrial sulfur dioxygenase. It is characterized by neurodevelopmental delay and regression, pyramidal and extrapyramidal signs, recurrent petechiae, chronic diarrhea, and orthostatic acrocyanosis. Laboratory findings include elevated serum levels of lactate and C4‐C5 acylcarnitines, and elevated urinary excretion of ethylmalonic acid and C4‐C6 acylglycines, notably isobutyrylglycine and 2‐methylbutyrylglycine. These findings are attributed to deficiency of the mitochondrial sulfur dioxygenase resulting in toxic accumulation of hydrogen sulfide metabolites in vascular endothelium and mucosal cells of the large intestine. Medical management has thus far been directed toward decreasing the accumulation of hydrogen sulfide metabolites using a combination of metronidazole and N ‐acetylcysteine. More recently, orthotopic liver transplant (OLT) has been reported as a new therapeutic option for EE. Here, we report two additional cases of EE who achieved psychomotor developmental improvement after 7‐ and 22‐months following OLT. The second case serves as the longest developmental outcome follow‐up reported, thus far, following OLT for EE. This report provides additional evidence to validate OLT as a promising therapeutic approach for what was considered to be a fatal disease.